Design and Evaluation for C02 Laser Focus System for use in Treating the Skin Diseases. - AlhamÂ·adani, A. H.; Abdul-Hussin, R. S.; Aljumaily, A. R.; Awad, W.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Due to the importance of Laser usage in the field of skin diseases Like removing. the cicatrix (acne causes). skin lines, cone spots, two laser systems have underwent a study and evaluation for their use in treatingthe skin diseases. The research deals with desigrrating an optical system .The system is for concentrating the laser beam C02 with a wave length of 10.6 micrometer Descriptions of 1he system and value of the perfonnance by using the optical design program ZEMAX, operations to get a favorable design and a center of 0.005 micrometer Respectively in laboratory temperatttr.is appropriate for use in treating the skin diseases.